2015
DOI: 10.1021/acsami.5b08709
|View full text |Cite
|
Sign up to set email alerts
|

A pH- and Temperature-Responsive Magnetic Composite Adsorbent for Targeted Removal of Nonylphenol

Abstract: A pH- and temperature-responsive magnetic adsorbent [poly(N-isopropylacrylamide) grafted chitosan/Fe3O4 composite particles, CN-MCP], was synthesized for the removal of the endocrine-disrupting chemical nonylphenol. According to the structural characteristics (changeable surface-charge and hydrophilic/hydrophobic properties) of the targeted contaminant, CN-MCP was designed owning special structure (pH- and temperature-responsiveness for the changeable surface-charge and adjustable hydrophilic/hydrophobic prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(17 citation statements)
references
References 58 publications
(80 reference statements)
1
15
0
Order By: Relevance
“…The pseudofirst order model results showed that the adsorption rate, k ad , of spruce biochar decreased by increasing Q max (Table 3). The pseudo-second order kinetic model assumes that the rate-limiting step is the interaction between adsorbate and adsorbent, and it is usually used to describe chemical adsorption (Zhen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The pseudofirst order model results showed that the adsorption rate, k ad , of spruce biochar decreased by increasing Q max (Table 3). The pseudo-second order kinetic model assumes that the rate-limiting step is the interaction between adsorbate and adsorbent, and it is usually used to describe chemical adsorption (Zhen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A thermal and pH-responsive PNIPAM grafted COS/magnetite composite (COS-MCP), adsorbent was synthesized for the removal of nonylphenol (NNP) from water. [223] The pHresponsiveness was confirmed by the zeta potential-pH profile with a ≈9.5 isoelectric point. Under acidic conditions, the primary amino groups of pH-sensitive chitosan are positively charged, these ammonium ions then become unprotonated gradually as pH rises.…”
Section: Multi-stimuli Responsive Adsorbentsmentioning
confidence: 94%
“…A contact angle study carried out at 20 and 40 °C proved the thermal-responsive nature of CN-MCP, with a water contact angle of 9.24° at 20 °C, that increased to 50.34° at 40 °C. [223] Thus, it could be inferred that the better adsorption performance of CN-MCP at 20 °C, was possibly due to the formation of a more hydrophilic form of NNP than at 40 °C. A slight decrease in CN-MCP particle size from 3.36 µm at 20 °C to 3.13 µm at 40 °C was due to collapsed branches, rather than extended branches of the hydrophobic PNIPAM as the temperature was above the LCST of PNIPAM (30 and 35 °C).…”
Section: Multi-stimuli Responsive Adsorbentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The crystallinity of SMC, SMC/Fe, and SMCB/Fe before and after adsorption was investigated using the XRD technique, as shown in Figure 3. The composite XRD patterns include various diffraction signals at 2 thetas of 12,15,20,22,25,29,30,32,35,38,40 , and 66 • . Figure 2C shows that the XRD signals are caused by the presence of crystalline magnetic biochar on the surface of biochar.…”
Section: X-ray Diffractometer (Xrd)mentioning
confidence: 99%